Reliable copper and aluminum connections for high power applications in electromobility - Hofmann, Konstantin; Holzer, Matthias; Hugger, Florian; Schmidt, Michael; Roth, Stephan (Physics Procedia, 2014)
Investigations concerning the growth of intermetallic phases during the heat input both at the diffusion annealing of copper aluminum roll claddings and the subsequent welding process of copper-aluminum connections by using roll cladded inserts are compared to the analytical determination of phase growth. The temperature distribution in the cladding interface has been determined by thermal simulation, in order to calculate the growth of the intermetallic phases. A comparison between the width of the phases in the analytical calculation and the experiment is achieved. In consideration of high welding speeds, the energy input during the welding process is appraised in order to grade the growth of intermetallic phases. Furthermore the prevention of damage in the roll cladding interface by means of unadapted material thicknesses or welding parameters can be assessed analytically and numerically. The numerical simulations can determine the critical thickness of the roll cladding to avoid damage like exceeding growth of intermetallic phases.
Created from Fastlane, Scopus look-up
Keywords: Aluminum; Copper; Diffusion; Heat conduction; Laser welding; Power electronics; Roll cladding